Erosive lichen planus: a therapeutic challenge - Williams Romero; Laura Giesen; Lucas Navajas-Galimany; Sergio Gonzalez (Sociedade Brasileira de Dermatologia, 2016)
Abstract Erosive lichen planus is an uncommon variant of lichen planus. Chronic erosions of the soles, accompanied by intense and disabling pain, are some of its most characteristic manifestations. We present the case of a woman who developed oral and plantar erosive lichen planus associated with lichen planus pigmentosus and ungueal lichen planus that were diagnosed after several years. The patient failed to respond to multiple therapies requiring longstanding medication but remained refractory. Knowledge of the treatment options for erosive lichen planus is insufficient. Further research is required to clarify their effectiveness, ideally adopting an evidence-based methodology.